Kearifan Lokal Iriban sebagai Upaya Konservasi Mata Air di Desa Lerep Kecamatan Ungaran Barat Kabupaten Semarang - Fithri, Aulia Syafira; Hilmy M. A. F, Jihan Ihza; Fitriana, Dwi Afni; Mutiara R, Zalza Bela; Wijayanto, Pradika Adi (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
One natural resource that is important to maintain is water. The increase in human population will certainly cause the need for drinking water to be very large, so water resource conservation efforts are needed which are realized in local wisdom implemented by rural communities, such as Lerep Village which is known for its Iriban local wisdom. This research aims to understand the procession of Iriban local wisdom and analyze the implementation and impact of Iriban local wisdom in spring conservation efforts in Lerep Village. This research uses qualitative descriptive research with a purposive sampling technique. Data collection techniques use observation, interviews, and documentation, and data analysis techniques use qualitative descriptive analysis. The research results show that (1) The Iriban tradition is one of the tourism products offered in Lerep Village to maintain and conserve water in the village area. (2) The Iriban tradition has two main phases, namely preparation and implementation of the tradition. (3) The Iriban tradition has a positive impact, namely a source of clean water in the village that is always available.